Regulating the Wild West: Symbolic Security Bubbles and White Collar Crime in the Art Market. Issue 1 (January 2022) - Oosterman, Naomi; Mackenzie, Simon; Yates, Donna
The study of crime and criminality in the art market has received increasing attention within criminology, however little has been written on the criminogenic values built into the structure of the art market. Despite increasing legislation to counteract instances of money laundering and fraud, the legal governance of the art market brings such ambiguity that actors in the market have formed their own responses to managing risk. In this article, we discuss how these actors rely on security bubbles and self-regulation and how this can have the unfortunate effect of adding to a criminogenic art market where white-collar crime is sustained. The dependence on self-policing created a field where powerful elites run things, and traditional policing agents have little purchase.